Alternaria youyangensis sp. nov. (Ascomycota: Pleosporaceae) from leaf spot of Fagopyrum esculentum in China - Huang, Jia Hui; Gou, Ya Nan; Nwe, Zin Mar; Aung, Sein Lai Lai; Deng, Jian Xin; Li, Mei Jia (Phytotaxa, 2024)
Alternaria is a widely distributed fungal genus as saprophytes, endophytes, and pathogens. An Alternaria species was isolated from the leaf spot of Fagopyrum esculentum in Banxi Town, Youyang County, Chongqing municipality, China. The obtained strains were determined based on morphological characteristics and multi-locus phylogenetic analyses including the internal transcribed spacer (ITS) of the rDNA region, glyceraldehyde-3-phosphate dehydrogenase (GAPDH), translation elongation factor 1-alpha (TEF1), RNA polymerase second largest subunit (RPB2), a major Alternaria allergen (Alt a 1), endopolygalacturonase (EndoPG) and an anonymous region gene (OPA10-2) gene sequences. The results indicate that the present species is a novel species, which is described and illustrated as Alternaria youyangensis sp. nov. in this study.